MENGASAH BAKAT DAN POTENSI KEBAJIKAN : PELAJARAN DARI SURAH AN-NAHL AYAT 78, SURAH ASY-SYAMS AYAT 8-10 DAN SURAH AL-ISRA AYAT 32 - Lilik Erni Suryani; Muhammad Rifqi Maulana; Annisa Layinal Hijja; Ana Rahmawati (CV. Adiba Aisha Amira, 2025)
This abstract aims to explain the potentials contained in the verses of thr Qur’an that inspired and motivate human self-developemnt. The problem raised is how the potential contained in surah An-Nahl verse 78 which discusses the physical and mental development of humans starting from the womb, with a focus on basic abilities such as hearing, sight and reason, all of which are intended to increase human awareness and gratitude for the grace of Allah, as well as the potential contained in surah Asy-Syams verses 8-10 whish will give birth to good and behavior in each individual, according to how they use inspiration from Allah’s prohibiton to approach zina, this prohibition functions as a preventive measure to protect the honor of individuals and families, and prevent wider social damage. This study uses a library research method with a descriptive approach, as well as data collection techniques through documentation. The results of the analysis show that the Qur’an reminds us of Allah’s blessings and the importance of using them wisely. These verses also teach noble and responsible behavior, and encourage awareness to maintain self-honor and family. By understanding the potential contained their abilities and live a more meaningful life. This study is expected to provide a positive contribution in understanding the moral and spiritual values contained in the Qur’an as a guide in developing self-potential.